Hypothetical Learning Trajectory Logaritma Berbasis Pendidikan Matematika Realistik Indonesia terhadap Kemampuan Pemahaman Konsep - Patmala, Kiki; Deswita , Ria; Ningsih , Febria (Universitas Islam Jember, 2025)
The ability to understand concepts is a crucial skill for comprehending, providing examples, and applying concepts, thereby fostering meaningful learning. However, students’ mathematical conceptual understanding is still relatively low. To achieve meaningful learning, improvements are necessary through a specific approach, namely the Indonesian Realistic Mathematics Education (PMRI). In achieving learning objectives, lessons need to be well-designed, one of which is through the Hypothetical Learning Trajectory (HLT). This study designs an HLT for logarithm concepts using the PMRI approach to improve students’ mathematical conceptual understanding at a high school (SMA/MA) in Sungai Penuh City, Jambi Province, employing a design research method. The research instruments include Student Activity Sheets, questionnaires, and conceptual understanding tests. The data collection techniques consist of interviews, observations, tests, and documentation. The research results indicate that the designed HLT is valid, and students can discover the concept of logarithms. After learning with the PMRI approach, students’ responses to PMRI reached 75.5%, while their mathematical conceptual understanding after the PMRI approach was categorized as high for 46.7% of students, moderate for 36.7%, and low for 16.7%. Keywords: Hypothetical Learning Trajectory, Logaeitma, Indonesian Realistic Mathematics Education, Understanding Concepts